Sintesis Tris(Thiophen)n-butil Germanium melalui Reaksi Arilasi Senyawa Thiophen dengan n-butil Germanium - Lesbani, Aldes; Mohadi, Risfidian (Sains & Matematika, 2013)
The arylation of 2-iodo thiophene and 3-iodo thiophen with n-butyl germanium using complex palladium as catalyst in argon atmospheric condition was carried out. Products of arylation were tris(2-thiophene)n-butil germanium (1) and tris(3-thiophene)n-butil germanium (2). Compounds (1) and (2) were characterized using GC-MS, 1H and 13C NMR. The results showed that compounds (1) and (2) were colorless oil with the yield 20% and 25%, respectively. Both (1) and (2) have m/z 380. Measurement using 1H NMR gave different peaks of proton equivalent between (1) and (2) while 6 equivalent protons in (1) and 7 equivalent protons in (2). The measurement using 13C NMR gave 8 equivalent carbons both for compound (1) and (2).